(untitled) (Research, Society and Development, 2021)
Objective: to describe the application of deliberative bioethics to ethical problem solving in the context of COVID-19. Method: this is a descriptive study, of the ethical case type, with a qualitative approach, developed from March to May 2020, in the curricular component of Biosafety, Ethics and Bioethics, of the Nursing Residency Program with Emphasis in Cardiology, of the Federal University of the Recôncavo da Bahia. Results: The analysis of the proposed case was carried out through the following steps of the deliberative process: Deliberation on facts (presentation of the case and clarification of the facts); Deliberation on values: identification of the moral problems of the case; Indication of the fundamental moral problem and identification of the values in conflict; Deliberation on duties (identification of the extreme, intermediate and optimal courses of action); Deliberation on responsibilities (submitting the optimal course of action to the tests of time consistency, publicity and legality). Conclusion: the use of the deliberative process in everyday ethical problems stimulates the transformation of professional practice in pursuit of prudent decisions, allowing facts to be explored, values to be identified, and duties to be performed.